Pengaruh Model Pembelajaran Student Created Case Studies terhadap Hasil Belajar Siswa pada Mata Pelajaran PAI BP di SMK Negeri 1 Tilatang Kamang - Haikal Hamdul Kamil; Puti Andam Dewi (YASIN, 2026)
Low student learning outcomes in Islamic Religious Education and Character Education remain a concern in various studies, but research that specifically discusses the application of the Student Created Case Studies (SCCS) learning model to the material on Etiquette in Using Social Media in vocational high schools remains limited. This study aims to analyze the effect of the Student Created Case Studies learning model on students’ learning outcomes in Islamic Religious Education and Character Education in Grade XI at SMK Negeri 1 Tilatang Kamang. This study used a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type, involving 38 students selected using saturated sampling. Data were collected through learning outcome tests in the form of pre-tests and post-tests, observation, interviews, and documentation, and were then analyzed using descriptive and inferential statistics through an Independent Sample t-Test with the assistance of IBM SPSS Statistics. The results show that the application of the Student Created Case Studies learning model has a positive and significant effect on students’ learning outcomes. This is indicated by the higher average post-test score of the experimental class compared with the control class, namely 80.43 and 66.90, with a significance value of 0.000 (< 0.05). The conclusion of this study emphasizes that the Student Created Case Studies learning model is effective in improving students’ learning outcomes in Islamic Religious Education and Character Education. These findings contribute to the development of student-centered case-based learning and encourage active participation, critical thinking skills, collaboration, and problem-solving in the learning process.